PENDAMPINGAN PEMBUATAN OVERALL JUMPSUIT APD GOWN, PENCARIAN SUMBER DANA DAN MANAJEMEN DISTRIBUSI KE RUMAH SAKIT - Fr. Ninik Yudianti; F.A. Joko Siswanto; Fr. Reni Retno Anggraini (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2020)
The activities of service were to provide assistance in the making of the Overall Jumpsuit APD Gown, funding management and distribution. There are three partners involved in this service, namely Partner-1: Gavrilla Fashion Studio, Partner-2: Sanata Dharma alumni and other donors, and Partner-3: Panti Rapih Hospital and small hospitals in Yogyakarta and its surroundings.The steps in service incclude a. Conducting discussions with a designer-entrepreneur for the manufacture of the Overall Jumpsuit APD needed by the hospital, b. Providing assistance in making the Overall Jumpsuit APD Gown: Selection of APD models, taking pictures, etc. c. Mentoring in raising funds to purchase raw materials and paying up tailors, and d. Mentoring for the distribution of Overall Jumpsuit APD Gowns that were handed over to the hospitals in need.The result of services, Gavrilla Fashion Studio, could produce large quantities of standard APD Overalls Jumpsuit. The making of APD was supported by many donors to buy materials and pay for sewing fees. The finished goods of APD were distributed and collected by the user's hospital.